Refugees, returnees and healing of traumatized communities - Ajduković, Dean (Array, 2004)
Refugees and internally displaced people are the largest population affected by the wars fought in the last decade in the South East Europe. About 2 million people from this region have been uprooted during the period of several years. In the psychological realm, the associated consequences included traumatized whole communities, high levels of anger and bitterness, mixed with fear, hopelessness and uncertainty. Once the refugees were physically safe, other needs emerged, both existential and psychological that were typically frustrated for a prolonged period of time. While being refugees, the people are often held in a dependent position by the authorities that often leads to learned helplessness. However, the resettlement process also puts former refugees in an ambivalent position. While strongly attracted to the original communities, at the same time there are forces that make them look for alternatives. The expectation that returning home will be only healing reflects the naï ve belief that communities will be the same as before the war, profound denial, search for disrupted personal and group identity and destroyed social networks. On the contrary, facing the reality of the own destroyed community is a highly retraumatizing. In the original communities they often face the people that they consider responsible for own suffering. Many people keep searching for missing family members, making them psychologically and socially vulnerable. Under such circumstances efforts that meet the needs of individuals and facilitate social reconstruction of the traumatized refugee community are essential. These programs should promote individual and community change, beyond focusing on trauma symptoms reduction. Community-based interventions address a variety of needs of large populations and the main healing functions of a community are put to use - to contain and support both family systems and the individual members. This strategy is based on the assumption that suffering caused by violence perpetrated in the community require several levels of interventions that lead to healing. This will was illustrated by the concept of the "Pyramid of Psychosocial Interventions". How to start re-establishing supportive environments under circumstances where the very notion of belonging to a community has been traumatically disrupted was illustrated.